PEMANFAATAN TEPUNG KOMPOSIT BERBASIS UBI UNGU DAN KEMBANG KOL DALAM PEMBUATAN FOOD BAR BEBAS GLUTEN - Lucia Crysanthy Soedirga (Universitas Pelita Harapan, 2021)
The food bar is a product that widely consumed due to its convenience and nutritious. The food bar commonly made from the wheat flour; however, other ingredients such as cauliflower and purple sweet potato can use as an alternative to make a gluten-free food bar. In this research, purple sweet potato and cauliflower were processed into composite flour within ratio 100:0; 90:10; 80:20; 70:30; 60:40; and 50:50. The result has shown that 90:10 of purple sweet potato flour and cauliflower was selected as the preferred ratio to make gluten free food bar. This food bar has hardness value of 983.32±1.39. The scoring result aroma, mouthfeel, texture, and taste were 2.98±1.14 (slightly not odd aroma); 3.73±1.04 (slightly not dry); 3.65±1.19 (slightly not easy to be broken); 2.93±1.23 (slightly not odd taste). Meanwhile, the degree of acceptance from panelist was neutral to slightly like toward aroma, mouthfeel, texture, taste, and overall acceptance of food bar within the value 4.80±1.11; 4.65±1.19; 4.40±1.19; 4.78±1.21; and 4.70±1.14, respectively. Moreover, it has 16.89±0.55% of moisture, 2.92±0.11% of ash, 11.01±0.11% of protein, 18.12±0.50% of fat, 51.06±0.11% of carbohydrate (by difference), and 10.82±0.07% of dietary fibre.